2006
DOI: 10.1209/epl/i2006-10288-0
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation scenarios for wetting transition on textured surfaces: The effect of contact angle hysteresis

Abstract: The wettability of textured surfaces is strongly dependent on the contact state of a small drop deposited on them. We consider transitions via nucleation between two representative contact states of Cassie and Wenzel when there exists hysteresis in the contact angle. We find that the effect of the hysteresis is significant: a drop can be trapped by various states which are neither Cassie nor Wenzel states in the conventional sense.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 36 publications
(24 reference statements)
1
38
1
Order By: Relevance
“…In contrast, it was suggested that the Cassie-Wenzel transition occurs via a nucleation mechanism starting from the drop centre (Ishino & Okumura 2006). Patankar (2010) in his recent theoretical investigation supposed that both mechanisms of WT (i.e.…”
Section: Dimension Of Wetting Transitionsmentioning
confidence: 99%
“…In contrast, it was suggested that the Cassie-Wenzel transition occurs via a nucleation mechanism starting from the drop centre (Ishino & Okumura 2006). Patankar (2010) in his recent theoretical investigation supposed that both mechanisms of WT (i.e.…”
Section: Dimension Of Wetting Transitionsmentioning
confidence: 99%
“…The exact value of the energy barrier and the mechanism of the transition to wetted regime are still being discussed [32,34,35]. The following criterion, which has been used by Patankar [32] and Barbieri et al [36] up to now, is applied for predicting transition energy barrier, dE, in this paper:…”
Section: Metastable-stable Wetting Transitionmentioning
confidence: 99%
“…The mechanism of wetting transition on patterned surfaces has been extensively studied in recent years using experimental and theoretical approaches, [7][8][9][13][14][15][16][17][18][19] as well as rare-event type of computer simulations. [20][21][22][23][24][25] Continuum models were used to analyze the different wetting regimes and the transition energy barriers.…”
Section: Introductionmentioning
confidence: 99%